Influence of Seed Priming and Foliar Spray on Seed Germination, Seedling Growth, Total Carbohydrate and Protein Content of Resultant Rice (Oryza Sativa L.) Seeds Under Salinity - MANASA HM; SR DODDAGOUDAR; BASAVE GOWDA; SHAKUNTALA NM; MAHANTASHIVAYOGAYYA K; LAKSHMIKANTH (Seed Research, 2026)
A study was conducted to investigate the influence of seed priming and foliar spray of sodium nitroprusside (SNP), potassium nitrate (KNO3), salicylic acid (SA) and gibberellic acid (GA3) on seed germination, seedling growth, total carbohydrate and protein content of the resultant rice seeds produced under a saline block of ARS, Ganavathi, UAS, Raichur. Among the treatments imposed, seed priming (0.43 mM )+ foliar spray (150 ppm) with gibberellic acid (GA3) significantly increased the total carbohydrate (81.3 mg g-1) and protein content (8.6%) of the resultant seed. This treatment also recorded significantly high seed germination (95.5%), shoot length (9.51 cm), root length (16.9 cm), seedling dry weight (90.4 mg) and seedling vigor index I (2522) compared to hydropriming and control.. These results indicate the use of GA3 in mitigating salt stress due to better seed germination and seedling growth by enhanced antioxidant activity, growth and assimilation of photosynthates. The other chemicals SNP,SA and KNO3at specific doses positively affected seed quality attributes compared to control.